Estimation of the Tilt of the Stellar Velocity Ellipsoid from RAVE and Implications for Mass Models - Siebert, A; Bienaymé, O; Binney, J; Bland-Hawthorn, J; Campbell, R; Freeman, K; Gibson, B; Gilmore, G; Grebel, E; Helmi, A; Munari, U; Navarro, J; et al. (2008)
We present a measure of the inclination of the velocity ellipsoid at 1 kpc below the Galactic plane using a sample of red clump giants from the RAVE DR2 release. We find that the velocity ellipsoid is tilted towards the Galactic plane with an inclination of 7.3 +/-1.8 degree. We compare this value to computed inclinations for two mass models of the Milky Way. We find that our measurement is consistent with a short scale length of the stellar disc (Rd ~2 kpc) if the dark halo is oblate or with a long scale length (Rd~3 kpc) if the dark halo is prolate. Once combined with independent constraints on the flattening of the halo, our measurement suggests that the scale length is approximately halfway between these two extreme values, with a preferred range [2.5-2.7] kpc for a nearly spherical halo. Nevertheless, no model can be clearly ruled out. With the continuation of the RAVE survey, it will be possible to provide a strong constraint on the mass distribution of the Milky Way using refined measurements of the orientation of the velocity ellipsoid.